2018
DOI: 10.5888/pcd15.180182
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Individual and Intimate Partner Factors and Cervical Cancer Screening in Kenya

Abstract: IntroductionCervical cancer is the most prevalent cancer among women in Kenya. Although cervical cancer screening could reduce illness and death, screening rates remain low. Kenyan women’s individual characteristics and intimate partner factors may be associated with cervical cancer screening; however, a lack of nationally representative data has precluded study until recently. The objective of our study was to examine individual and intimate partner factors associated with cervical cancer screening in Kenya.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
3
19
0
3
Order By: Relevance
“…In other developing regions such as African countries, cervical cancer screening plans have led to better cervical cancer outcomes, as cervical cancer planning is an important type of disease prevention . Despite the health benefits of such type of disease prevention, cervical cancer screening rates remain low in Kenya, a dynamic developing country in Africa. Similar circumstances are evident in China, with 7% utilization rate of preventive care services among adults .…”
Section: Discussionmentioning
confidence: 83%
“…In other developing regions such as African countries, cervical cancer screening plans have led to better cervical cancer outcomes, as cervical cancer planning is an important type of disease prevention . Despite the health benefits of such type of disease prevention, cervical cancer screening rates remain low in Kenya, a dynamic developing country in Africa. Similar circumstances are evident in China, with 7% utilization rate of preventive care services among adults .…”
Section: Discussionmentioning
confidence: 83%
“…One other important individual barrier, determined in the present study, was worries associated with women's privacy. Three other studies in Africa demonstrated that emotional (defined as fear or shyness), embarrassment, painful procedure, possible violation of privacy, and reliance on prayer with the onset of illness were the major factors preventing women from attending the screening services (Dutta, Haderxhanaj, & Agley, 2018, Kangmennaang et al, 2018Lim & Ojo, 2017).…”
Section: Individual Community Health Provider and Health System Barriers To Cervical Cancer Screening Servicesmentioning
confidence: 99%
“…23 , 26 , 27 , 46 , 53 , 55 , 56 , 59 , 60 As Protestants are a relatively heterogeneous religious group that is divided into various subgroups, this denomination was handled quite differently among the studies: n=4 investigated Protestants in general. 46 , 53 , 56 , 60 In sum, n=2 studies differentiated between Mainline and Evangelical Protestants, 23 , 26 one between Baptists, Methodists, and the Holiness movement 48 and the other one between Presbyterians and Methodists. 55 Finally, n=2 studies regarded members of the Pentecostal movement, 59 , 60 and n=1 rated Apostolic sects as an independent subcategory.…”
Section: Resultsmentioning
confidence: 99%